An Overview of Immune Evasion Strategies of DNA and RNA Viruses - Naz, Sheikh S.; Aslam, Afsheen; Malik, Taqdees (Infectious Disorders - Drug Targets, 2021)
A successful viral infection is due to the effective evasion of viruses of the immune system. The entry of viruses is usually detected by different cellular receptors including PRRs. Recognition of the viral genome leads to the production of interferons through a signaling stream. This review article provides brief information regarding escape mechanisms of DNA and RNA viruses from the host immune system. These strategies include viral endonuclease activity, cap snatching of host mRNA, the formation of replication organelles, stress granule formation, membrane modifications, action of proteases, and evasion from ISGs. Moreover, the strategies of DNA viruses to inhibit immune responses include subversion of mRNA, transcriptional factors, adaptor proteins, PRRs, evasion from T lymphocytes, genomic diversity, theft or seizure of host defense proteins, imitation of host factors like affecting cytokines and chemokines of the host, suppression or inhibition of apoptosis, and proteasomal degradation of host antiviral proteins by DNA viruses. The knowledge of these mechanisms is pivotal to understanding different methodologies that viruses have created to escape antiviral cellular reactions of the host as well as virus-host interactions and the origin of viral pathogenesis. Also, this knowledge is significant for the design of gene targeting vectors, antiviral vaccines, and the development of effective treatments directed against DNA and RNA viruses.
Keywords: coronaviruses